Higgs-mediated optical amplification in a nonequilibrium superconductor - Buzzi, M; Jotzu, G; Cavalleri, A; Cirac, JI; Demler, EA; Halperin, BI; Lukin, MD; Shi, T; Wang, Y; Podolsky, D (American Physical Society, 2021)
We propose a novel nonequilibrium phenomenon, through which a prompt quench from a metal to a transient superconducting state can induce large oscillations of the order parameter amplitude. We argue that this oscillating mode acts as a source of parametric amplification of the incident radiation. We report experimental results on optically driven K3C60 that are consistent with these predictions. The effect is found to disappear when the onset of the excitation becomes slower than the Higgs-mode period, consistent with the theory proposed here. These results open new possibilities for the use of collective modes in many-body systems to induce nonlinear optical effects.